Integrasi Literasi Matematika dan Pemikiran Komputasi: Strategi Penguatan Kompetensi Digital Dalam Pendidikan Abad Ke-21 - Ariq, Andi; Nursalam; Sri Sulasteri; Andi Kusumayanti (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2025)
The digital revolution has profoundly transformed economic, social, and cultural structures, demanding the emergence of new competencies such as mathematical literacy and computational thinking as essential foundations of 21st-century education. This study aims to analyze the conceptual interrelation and pedagogical implications of integrating these competencies within the context of learning in the digital economy era. Employing a qualitative exploratory approach through a systematic literature review, data were obtained from scholarly publications over the past decade that address the integration of mathematical literacy and computational thinking. The findings reveal that their integration enhances logical reasoning, problem-solving, and data-driven decision-making skills, while the adoption of artificial intelligence (AI) technologies further supports adaptive and reflective learning environments. Nevertheless, the success of this integration requires a holistic pedagogical framework grounded in humanistic values to prevent the decline of students’ critical and independent thinking abilities. Therefore, the integration of mathematical literacy and computational thinking can be viewed as a strategic transformation in education to cultivate digitally literate, creative, and adaptive generations prepared for the challenges of a knowledge-based economy.